Android JPEG File Carving with Geotag Analysis - Tam, Jia Cherng; Abdullah, Nurul Azma (Applied Information Technology And Computer Science, 2024)
In today’s digital age, recovering lost JPEG images from Android devices is crucial for preserving memories and supporting investigations. However, the lack of seamless integration between file carving and geotag analysis resulted in increased complexity of workflow and decreased productivity. This project developed an "Android JPEG File Carving with Geotag Analysis" tool to address this need. Using an object-oriented approach, the tool integrates file carving and geotag analysis techniques, implemented with Python. The target users for the tool are general consumers who want to recover their JPEG files from their Android smartphone’s physical image and even individuals interested in digital forensics, particularly mobile forensics. The tool successfully recovers JPEG files, extracts geolocation metadata, verifies integrity through hash comparisons, and generates comprehensive reports. These features streamline digital forensic analysis, offering a robust solution for both general consumers and forensic enthusiasts. The tool's user-friendly design, effective file carving and geotag analysis functionality, and other features such as hash generation and visualized map highlight its significance in mobile forensics.